2000
DOI: 10.1152/jn.2000.84.1.255
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Temporal Processing: Responses to Sinusoidally Amplitude-Modulated Tones in the Inferior Colliculus

Abstract: Time-varying envelopes are a common feature of acoustic communication signals like human speech and induce a variety of percepts in human listeners. We studied the responses of 109 single neurons in the inferior colliculus (IC) of the anesthetized Mongolian gerbil to contralaterally presented sinusoidally amplitude-modulated (SAM) tones with a wide range of parameters. Modulation transfer functions (MTFs) based on average spike rate (rMTFs) showed regions of enhancement and suppression, where spike rates incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
285
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(322 citation statements)
references
References 50 publications
(48 reference statements)
34
285
3
Order By: Relevance
“…Inhibitory circuitry may play a role in maintaining/enhancing synchronization to SAM tones (Frisina et al, 1994;Rhode and Greenberg, 1994;Zhao and Liang, 1995;Young, 1998;Backoff et al, 1999;Krishna and Semple, 2000;Hancock and Voigt, 2002b;Joris et al, 2004;Kanold and Manis, 2005;Street and Manis, 2007). The present findings from aged DCN output neurons resemble what is seen when inhibitory neurotransmission is blocked during temporal processing paradigms in CN and IC (Koch and Grothe, 1998;Backoff et al, 1999;.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Inhibitory circuitry may play a role in maintaining/enhancing synchronization to SAM tones (Frisina et al, 1994;Rhode and Greenberg, 1994;Zhao and Liang, 1995;Young, 1998;Backoff et al, 1999;Krishna and Semple, 2000;Hancock and Voigt, 2002b;Joris et al, 2004;Kanold and Manis, 2005;Street and Manis, 2007). The present findings from aged DCN output neurons resemble what is seen when inhibitory neurotransmission is blocked during temporal processing paradigms in CN and IC (Koch and Grothe, 1998;Backoff et al, 1999;.…”
Section: Discussionsupporting
confidence: 60%
“…At all temporal modulation depths, and at either age, buildup and pauser-buildup units have higher peak modulation sync functions than units showing widechopper temporal responses at all temporal modulation depths, and at either age. Thus the agerelated shift toward wide-chopper response types, a temporal response type with higher firing rates and a decreased ability to synchronize to a SAM envelop could explain the present findings and is consistent with a loss of glycinergic inhibition.Inhibitory circuitry may play a role in maintaining/enhancing synchronization to SAM tones (Frisina et al, 1994;Rhode and Greenberg, 1994;Zhao and Liang, 1995;Young, 1998;Backoff et al, 1999;Krishna and Semple, 2000;Hancock and Voigt, 2002b;Joris et al, 2004;Kanold and Manis, 2005;Street and Manis, 2007). The present findings from aged DCN output neurons resemble what is seen when inhibitory neurotransmission is blocked during temporal processing paradigms in CN and IC (Koch and Grothe, 1998;Backoff et al, 1999;.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Dependent on modulation frequency, changes in modulation depth could result in either suppression or enhancement of the rate responses. Thus, Krishna and Semple (2000) demonstrated that at the level of the inferior colliculus, some units can encode modulation depth. However, as outlined above, the envelope spectra differ substantially from those of our stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…7) indicate changes in the envelope spectra clearly exceeding the human 1 dB threshold. Krishna and Semple (2000) investigated responses of inferiorcolliculus neurons in the Mongolian gerbil to SAM tones varying in both modulation frequency and modulation depth. They showed that the rate modulation transfer function depended significantly on modulation depth.…”
Section: Discussionmentioning
confidence: 99%